Etika Profesi Advokat Dalam Menangani Perkara Hukum Menurut Perspektif Hukum Islam - Rudi Pratama; Adji Prasetia; Fauziah Lubis (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Advocate is a noble profession (officium nobile). The main task of an advocate in court is to present facts and considerations that are related to the client he is defending in a case, thus enabling the judge to give the fairest decision. In order for an advocate to carry out his duties properly, it is necessary to have an advocate's guidelines in doing something, namely the existence of an advocate's code of ethics.islam is a perfect religion and regulates all human activities and human behavior. Advocate ethics are also regulated in Islam.This research is also known as library research, namely research conducted using library materials or library literature as written sources.In Islam, it is emphasized for law enforcers (advocates) to prioritize the value of justice when dealing with clients in resolving a legal case. In carrying out his profession, an advocate for clients must be based on mutual trust.This noble profession will be tarnished by deviant practices carried out by a few advocates in providing legal services to clients or the public, which will have a very significant negative impact on the organization and the profession.The ethics of an advocate in Islam must be fair, have a noble character, and speak polite and polite words, not dirty words. Keyword : Advocate, Proffesssion, Advocate code of ethics